Modernisasi dan Enkulturasi Budaya dalam Pendidikan Islam - Rudwi Hantoro, Ramandha; Rosnawati, Rosnawati; Saripuddin, Saripuddin; Milasari, Milasari; Lias Hasibuan; Kasful Anwar Us (Jurnal Ilmu Multidisiplin, 2022)
Globalization forces Islamic education as a system to continue to develop and adapt to the times, as well as proof that Islam has the principle of "Shólihun fí kulli zamánin wa makánin wa ummah". Therefore, the modernization and enculturation of Islamic education culture is an interesting issue to discuss. In this article, we will discuss theoretically using qualitative methods through library research on the modernization and enculturation of Islamic education culture in Indonesia. Critically, based on the data obtained in the form of qualitative data from various reading sources, books, articles, research, scientific publications and manuscripts for analysis. The results of the discussion show that Islamic education in Indonesia has experienced a clash of two paradigms, namely on the one hand it is affected by weternization and on the other hand it is affected by Arabization. With these two paradigms of view, Indonesian Islamic education creates its own Islamic "culture" that carries Indonesianness by internalizing Islamic values ??but at the same time has Middle-Eastern cultural values ??as the source of Islam itself and Western culture as the center of modernism.